PEMANFAATAN BATU PASIR LAUT WARNA HITAM TERAKTIVASI NaOH 4 N DAN TERSALUT Fe2O3 SEBAGAI ADSORBEN ION NITRAT - I Nengah Simpen; Putu Suarya; Komang Yogi Purnamawati (Jurnal Kimia (Journal of Chemistry), 2012)
The research about adsorption of nitrate ion was carried out by black sandstone that was activated by 4 N NaOH and coated by Fe2O3, and washed by aquades with coating pH variation of 5, 7 and 11. The aim of this research is to find the ability of modified sandstone adsorbent in decreasing nitrate ion concentration. This research included the determination of surface acidity by acid-base titration method, determination of the specific surface area by blue methylene method, determination of equilibrium time of adsorption, adsorption isotherms and adsorption capacity of sandstone on nitrate ions by UV-vis spectrophotometer. The results showed that the highest surface acidity came from the sandstone activated with 4 N NaOH and Fe2O3-coated (A1) which was 0.4423 mmol/g, where as the highest specific surface area was owned by sandstone activated with 4 N NaOH and with Fe2O3-coated pH 7 (A3), which was 21.2899 m2/gram. Isotherm patterns were classified in the Langmuir adsorption isotherm with r value 0.9895. The highest nitrate ion adsorption capacity of the adsorbent at pH 4.19 was 2.8333 mg/g in equilibrium time of 90 minutes. In this study, sandstone activated with 4 N and coated with Fe2O3 was able to provide higher capacity than the sandstone control.